Formação Sociocientífica na Licenciatura em Química: Discurso, Prática e Possibilidades - Moura, Francisco Marcôncio Targino de (2019)
It is important to study the formation of chemistry teachers and their teaching action, since in this moment of rapid change, science and technology play a prominent role for life in society. Socio-scientific training should be understood as the ability to relate chemical knowledge to social reality, reflecting on the interrelationships between science and technology within society, thus seeking to form critical citizens who are able to make a personal and social decision-making about the environment. problem situations related to science and technology. Our research had as its guiding question to understand if the degrees in Chemistry work the formation of teachers in a socio-scientific perspective as a means of dialogue between the scientific formation and its relation with the social context, providing the expansion beyond the historically instituted model of technical rationality. Our general objective was to investigate constitutive elements of a socio-scientific perspective in teacher education in Chemistry degrees, aiming to identify an integration and articulation of this formation with the knowledge and practices of teacher education. Specifically we seek to: a) Identify the perception of students and teachers of undergraduate degrees in chemistry about the importance of a socio-scientific formation in the curricular development of the course; b) Analyze the speeches of the teachers graduating in Chemistry regarding the orientation, planning and teaching action, related to the elements related to the socio-scientific perspective; c) Identify in the speeches of undergraduate students in chemistry if they perceive in their formation the presence of a socio-scientific perspective during the course curriculum development; d) To analyze the content of official and institutional documents that guide the formation of chemistry teachers, regarding the need for a socio-scientific formation; e) Understand the limits and possibilities of the curriculum development of a socio-scientific formation of undergraduates in Chemistry in the researched institutional contexts. Our research was of the qualitative type, where we chose as a method the Collective Subject Discourse (CSD), roughly consisting of the discourse of each subject participating in the research, giving rise to a discursive synthesis, which represents the qualitative thinking of the collectivity, presenting symbolically what the social collective of the research subjects thinks. The places of research were the Degrees in Chemistry of the Federal University of Ceará (UFC) and the State University of Ceará (UECE). The collection and analysis of data obtained from documentary evidence, as well as in the teachers 'and students' DSC, provided us with clear and safe insights to answer the question that guided the thesis. The research carried out accurately and reliably reached the goals set at the beginning of the process to guide the walk and that were thought from the questions that guided this thesis. Given the above is that we defend the Thesis that the formation of graduated teachers in Chemistry privileges the technical-instrumental rationality and the disciplinary scientific knowledge, not substantially and continuously dialectizing these components with the socio-scientific and critical perspective in the formative processes. The research work carried out led us to the proposition of limits and possibilities for the accomplishment of a socio-scientific formation work in the Chemistry Degree in a more effective and safe way, as a result of the voices of the social teachers and students investigated.